Librarians as Critical Infrastructure in Data Ecosystems - Gradeck, Robert (International Journal of Population Data Science, 2018)
Across the US and around the world, a growing number of public sector, educational, and nonprofit organizations have been sharing data with one another. These organizations hope to increase transparency, enhance efficiency and service quality, improve communities, encourage public participation, develop new knowledge, and foster civic innovation. While there are many success stories around data sharing, there is a growing awareness that the act of publishing data will not always result in community impact. Data intermediaries are often needed to help people extract value from data, and to help producers make good decisions about what and how they publish. In Pittsburgh, our local civic data ecosystem is unique in that both public and academic librarians are actively involved as data intermediaries, and they work in close collaboration with other intermediaries, data publishers and users in a variety of ways. Librarians play a number of roles, including helping people discover information, building data literacy and technical skills, providing technical assistance in data management and documentation, creating feedback mechanisms to publishers, convening and hosting events, and connecting data users. Our experience shows that libraries and librarians should be key actors in the continuing development of data ecosystems and act as core data intermediaries; their expertise adds value to a wide range of issues that affect both data publishers and users. In this talk, I will share insights gained through the Civic Switchboard project, which aims to develop the capacity of libraries in civic data ecosystems.